Early Diagnosis of Head and Neck Malignancies - Mustafa, Osman M EL (مجلة الجزيرة للعلوم الصحية; مجلد 10 عدد 2 (2014), 2014)
Head and neck cancer is the leading cancer among Sudanese male population.Prognosis in malignancy in general is better when early diagnosis is made and no doubt in many cases 100% 5-year survival rate or cure can be achieved with early diagnosis and appropriate management.Early diagnosis can be achieved in a few head and neck malignancies such as nasopharyngeal carcinoma, hypo pharyngeal carcinoma, carcinoma of the oral cavity and carcinoma of the larynx. Knowledge of the early symptoms and signs together with a high suspicion index is the key to early detection . In this review article, the author is reflecting his long experience over thirty years and his publications related to the subject of head and neck malignancies in the Gezira State which is inhabited by the bulk of the population of the central Sudan